Analisis Potensi dan Strategi Pengembangan Di Kawasan Mangrove Center Bengkak Kecamatan Wongsorejo Banyuwangi sebagai Daerah Ekowisata - Layinatuzarok Layinatuzarok; I Gusti Ngurah Putra Dirgayusa; Ni Luh Putu Ria Puspitha (Journal of Marine and Aquatic Sciences, 2023)
Ecotourism is one of the special tours where these activities pay attention to the environment and strongly support responsible tourism. Ecotourism is an environmental services in mangrove area of Bengkak Village, Wongsorejo District, are one of the unexploited natural resource potentials. The research aim to examine Mangrove ecosystem’s potential as an ecotourism destination and to establish a development strategy for Mangrove Center Bengkak. This research took place in the Mangrove Center Bengkak, Wongsorejo District, Banyuangi Regency, between February and April 2020. The descriptive exploratory survey method enable in this research, which included both primary data and secondary data. The interview method us in the research a list of questions (questionnaire) aimed at tourists, surrounding communities and managements. The data obtained were analyzed land suitability, area carrying capacity, implementation of the concepts of ecotourism and SWOT analysis. The result of the suitability analysis show that the Mangrove Center Bengkak, with a Tourism Suitability Index of 67 percent, is suitable to be used as an ecotourism area. Tourism activities in the Mangrove Center Bengkak area also have carrying capacity of 167 people per day. Mangrove Center Bengkak has implemented the principle of ecotourism. However, the application of these principles has not yet implemented properly. Its needs a lot improvement. The conclusion of this study is Mangrove Center Bengkak area has the potential for ecotourism development.